2020
DOI: 10.1002/elps.201900329
|View full text |Cite
|
Sign up to set email alerts
|

µ‐NMR at the point of care testing

Abstract: NMR shows strong analytical capability for obtaining molecular information on materials and is used in a variety of fields. Micro‐NMR (µNMR) is mainly based on low‐field NMR (LF‐NMR), which makes NMR detection portable and inexpensive. Point‐of‐care testing (POCT) has gradually become an area of major concern, and scientists have made much progress in applying µNMR systems for POCT. To the best of our knowledge, this is the first review of the latest development in miniaturization of µNMR systems. Then, we dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Furthermore, biomarkers of infection, prognosis, and those to guide and monitor therapy, could be different, which suggests the potential need for this type of analytical techniques after the biomarker discovery phase. With that in mind, there have been advances in the miniaturization of NMR equipment towards their application in point-of-care devices [35,36]. There are diverse studies of metabolomics of plasma, serum, or urine, that enabled to build good models to predict infection in relation to healthy volunteers, and infection among non-infected critically ill patients and patients presenting confound pathophysiological processes (e.g., mechanical ventilated patients, cancer patients with neutropenia, etc.,) (Table 1).…”
Section: Biomarkersmentioning
confidence: 99%
“…Furthermore, biomarkers of infection, prognosis, and those to guide and monitor therapy, could be different, which suggests the potential need for this type of analytical techniques after the biomarker discovery phase. With that in mind, there have been advances in the miniaturization of NMR equipment towards their application in point-of-care devices [35,36]. There are diverse studies of metabolomics of plasma, serum, or urine, that enabled to build good models to predict infection in relation to healthy volunteers, and infection among non-infected critically ill patients and patients presenting confound pathophysiological processes (e.g., mechanical ventilated patients, cancer patients with neutropenia, etc.,) (Table 1).…”
Section: Biomarkersmentioning
confidence: 99%
“…Other NATs are under development and a few are currently in use. These include CRISPR, isothermal amplification, and next-generation sequencing (NGS) (Broughton et al 2020 ; Guo et al 2020 ; Nat Biotechnol 2020 ; Weissleder et al 2020 ; Yoshikawa et al 2020 ). CRISPR-Cas12- and CRISPR-Cas13-based assays simultaneously perform reverse transcription and isothermal amplification from RNA extracted from nasopharyngeal or oropharyngeal swabs; then, it goes through Cas12 or Cas13 detection of coronavirus sequences with no cross reactivity from related coronavirus strains (Broughton et al 2020 ).…”
Section: Development Of Diagnosticsmentioning
confidence: 99%
“…181 ) Planar microcoils are easier to fabricate down to nL volumes and find applications in on-chip NMR devices. 182 Recently, Sahin Solmaz et al have demonstrated a silicon-chip-based device for DNP NMR of aqueous solutions of the TEMPO radical at room temperature. 183 A sample volume of about 1 nL is contained in a capillary that is placed over the double NMR/EPR microcoils.…”
Section: Instrumental Challenges and Outlook Formentioning
confidence: 99%